Protective Effect of Melatonin Against Polymicrobial Sepsis Is Mediated by the Anti-bacterial Effect of Neutrophils - Xu, Li; Zhang, Wei; Kwak, Minseok; Zhang, LiJun; Lee, Peter C. W.; Jin, Jun-O (Frontiers in Immunology, 2019)
Sepsis is an infection- or toxin-mediated systemic inflammatory syndrome. Previous studies have shown that melatonin, the primary hormone produced by the pineal gland, attenuates the effect of polymicrobial infection-mediated septic shock in animals. However, the mechanism of the anti-septic effect of melatonin during polymicrobial infection has not been well-studied. In this study, we investigated how melatonin protects mice from polymicrobial sepsis. Melatonin treatment inhibited peripheral tissue inflammation and tissue damage in a cecal ligation puncture (CLP)-induced polymicrobial sepsis model, consequently reducing the mortality of the mice. We found that macrophages and neutrophils expressed melatonin receptors. Upon depletion of neutrophils, melatonin-induced protection against polymicrobial infection failed in the mice, but melatonin treatment in macrophage-depleted mice attenuated the mice mortality resulting from polymicrobial sepsis. Moreover, melatonin treatment promoted the development of the neutrophil extracellular trap (NET), which contributed to anti-bacterial activity during polymicrobial infection, whereas the phagocytic activities of neutrophils were inhibited by melatonin. The data from this study support previously unexplained antiseptic effects of melatonin during a polymicrobial infection and could be potentially useful for human patients with sepsis.